اﻟﺘﺼﻮف اﻹﺳﻼﻣﻲ و اﻟﺮﻫﺒﻨﺔ)دراﺳﺔ ﻣﻘـﺎرﻧﺔ - ﺧﻨﻮﻓﺔ, ﺣﻨﺎن; ﻣﻠﻴﻚ, ﺣﻨﺎن; ﻟﻌﻮﻳني, ﻧﺼيرة (جامعة الوادي university of eloued, 2017)
ﻳﺘﻔﻖ ﻛﻞ ﻣﻦ اﻟﺘﺼﻮفاﻹﺳﻼﻣﻲواﻟﺮﻫﺒﻨﺔ في اﻟﻌﺪﻳﺪﻣﻦ المﻔﺎﻫﻴﻢ في ﻛﻮﻤﺎ يحﻤﻼن أﻋﻠﻰ درﺟﺎتالخﻠﻮة واﻟﻌﺒﺎدةإﻻأنﻫﺬا ﻻِ يمﻨﻊاﺧﺘﻼﻓﻬﻤﺎ في ﺑﻌﺾ المﺒﺎدئ والمﻌﺘﻘﺪات واﻟﺘﺼﻮف ّﻣﺼﻄﻠﺢ ﻳﻌﺮف ﻋﻨﺪ المﺴﻠﻤين ﺧﺎﺻﺔ ،أﻣﺎاﻟﺮﻫﺒﻨﺔ ﻓﻬﻲ ﺗﻘﺘﺼﺮ ﻋﻠﻰ المﺴﻴﺤﻴين ﺧﺎﺻﺔ،وﻣﻦ ﻫﻨﺎ ﻧﺴﺘﻨﺘﺞأّن اﻟﺘﺼﻮف اﻹﺳﻼﻣﻲ واﻟﺮﻫﺒﻨﺔ وﺟﻬﺎن ذا ﻋﻤﻠﺔ واﺣﺪة ﻳﺼﺒﺎن في ﻗﺎﻟﺐ اﻟﺘّ ﻌﺒﺪ واﻟﺘﻨﺴﻚ. Study Summary: Islamic Sufism and monasticism agree in many concepts in that they carry the highest dergrees of privacy and worship, but this does not perent their differences in some principles and beliefs. Sufism is a term known to Muslims, especially monasticism is limited to Christians in particular. Islamic and monasticism are tow sides of one coin that are molded in the form of worship and tusk.
مقارنة